Peranan Kepemimpinan dalam Meningkatkan Disiplin Kerja Pegawai Negeri Sipil (Studi pada Kantor Kecamatan Gondangwetan Kabupaten Pasuruan) - Pratiwi, Lia (Jurnal Administrasi Publik, 2013)
Abstract: The Role of Leadership In Increase Civil Public Servant Job Discipline (study on Gondangwetan’s district office Pasuruan). In daily life that was happen in world job stills a lot of clerk that its professionalism contemns, mark sense abuse in working and discipline reducing in obey the regulation that be present, therefore the role of the leader indispensable to increase their job discipline and be reached the aim of organization already been formed. The purpose of this study was to know the role of leadership in increase  servant job diciplin and constraints. This research uses descriptive qualitative research approach. The result of research that doing showed that leader role in increase clerk job discipline was said with consideration, those roles cover by follow the ceremony in the morning, meeting once a week, reward’s application, internal monitoring to staff and socialization PP  No . 53 tahun 2010 about clerk discipline. In order to realize the good discipline in Gondangwetan District, directly the District Head should be monitoring to his subordinate without waiting for the report from section head, the District Head should give high motivation and direction to his subordinate, and in contrast, the District Head should pay more attention for employee’s prosperity, for example give the bonus for the discipline and good performance employee and in contrast, will give punishment if the employee break the law. Keyword: role of leadership, dicipline, civil public servant Abstrak: Peranan Kepemimpinan Dalam Meningkatkan Disiplin Kerja Pegawai Negeri Sipil (Studi pada Kantor kecamatan Gondangwetan kabupaten pasuruan). Dalam kehidupan sehari-hari yang terjadi dalam dunia kerja masih banyak pegawai yang profesionalismenya rendah, adanya penyalahgunaan waktu kerja dan kurangnya displin dalam mentaati peraturan yang ada. Tujuan dari penelitian ini adalah untuk mengetahui peranan kepemimpinan dalam meningkatkan disiplin kerja pegawai dan hambatannya. Penelitian ini menggunakan jenis penelitian kualitatif. Hasil dari penelitian ini adalah peran pemimpin dalam meningkatkan displin kerja pegawai sudah dikatan dengan baik, peran tersebut meliputi pelaksaan apel pagi, rapat setiap seminggu sekali, pemberian reward, pengawasan internal kepada staf dan sosialisasi PP No. 53 tahun 2010. Agar kedisiplinan di Kecamatan Gondangwetan terwujud dengan baik sebaiknya Camat melakukan pengawasan secara langsung kepada bawahannya tanpa menunggu laporan dari kepala seksi, Camat harus memberikan motivasi yang tinggi dan pengarahan kepada bawahan, dan sebaiknya Camat lebih memperhatikan masalah kesejahteraan pegawai misal diberi bonus kepada pegawai yang disiplin dan diberi hukuman jika melanggar.Kata kunci: peranan kepemimpinan, displin, pegawai negeri sipil